5(x+3)-3=2(x+8)

Simple and best practice solution for 5(x+3)-3=2(x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+3)-3=2(x+8) equation:


Simplifying
5(x + 3) + -3 = 2(x + 8)

Reorder the terms:
5(3 + x) + -3 = 2(x + 8)
(3 * 5 + x * 5) + -3 = 2(x + 8)
(15 + 5x) + -3 = 2(x + 8)

Reorder the terms:
15 + -3 + 5x = 2(x + 8)

Combine like terms: 15 + -3 = 12
12 + 5x = 2(x + 8)

Reorder the terms:
12 + 5x = 2(8 + x)
12 + 5x = (8 * 2 + x * 2)
12 + 5x = (16 + 2x)

Solving
12 + 5x = 16 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
12 + 5x + -2x = 16 + 2x + -2x

Combine like terms: 5x + -2x = 3x
12 + 3x = 16 + 2x + -2x

Combine like terms: 2x + -2x = 0
12 + 3x = 16 + 0
12 + 3x = 16

Add '-12' to each side of the equation.
12 + -12 + 3x = 16 + -12

Combine like terms: 12 + -12 = 0
0 + 3x = 16 + -12
3x = 16 + -12

Combine like terms: 16 + -12 = 4
3x = 4

Divide each side by '3'.
x = 1.333333333

Simplifying
x = 1.333333333

See similar equations:

| 43-4=y | | 9h-16=74 | | 9m-15=58 | | 5n^2+7n=-2 | | 8x+12y-20= | | 40+16x= | | 3(25-10h+h^2)-20+4h-(75-20)= | | 15x-28= | | 0=x^2-16x-225 | | 6x+27= | | x^7=65 | | 4.9x^2-20x=0 | | 8+(y+2)=4(y-3) | | x+(x*0.25)=500000 | | 3n+4-4=n+20 | | 4t^2-9s^2=0 | | lnx^2-6lnx+5=0 | | (5x-2)-(3x-1)=(4x+3)-(5x-2) | | 7(-1+h)-5(-1)= | | 2lnx+ln(2x-3)=ln(3x-2) | | 0.63=logx | | 3(-5+h)-4(-5)= | | 3(25-2h+h^2)-4+4h-(4-3)= | | 9b^2+42bg+49g^2= | | 3(25-2h+h^2)-4+4h-(3-4)= | | 7(1-2h+h^2)-5+5h-(7-5)= | | 20n=60 | | y=192+1.04y | | 14+r=33 | | 5ab-8abc=0 | | 12+8+x+y=50 | | 4x+8x=109 |

Equations solver categories